(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Assessment has always been playing a vital role in determining the efficacy of Englishlanguage courses around the globe. In view of the importance of having integration of skills in Englishlanguage lessons, proper and constructive feedback sessions are very essential to see what the pitfallsare in applying the practices in ELT lessons especially in online lessons. Keeping this in mind, mockexams are becoming increasingly popular in academic institutions as a means of evaluating students’preparedness for their final exams. However, feedback on students’ performance in mock exams can beseen as both a blessing and a curse. On the one hand, feedback can help students identify areas ofweakness, adjust their study strategies, and improve their performance in the final exam. In a study byEl-Helou and colleagues (2016), it was found that feedback provided to medical students after mockexams significantly improved their final exam scores. On the other hand, receiving negative feedbackcan be demotivating for students, leading to lower self-confidence and decreased engagement with thematerial.In another study by Könings and colleagues (2019), it was found that the quality of feedback provided byinstructors was a key factor in determining its effectiveness. Instructors who provided detailed andspecific feedback were more likely to positively impact students’ performance, while generic feedbackhad little effect.This paper explores the potential benefits and drawbacks of providing feedback on students’performance in mock exams. It reviews the existing literature on the topic, discussing the psychologicaleffects of feedback on students, as well as the impact on their academic performance. Additionally, itexamines the role of the instructor in providing feedback and the importance of balancing constructivecriticism with positive reinforcement. The sample for this study is study collected from the students‘community at University of Technology and applied Sciences at Ibra, Oman.The findings suggest that feedback can be an effective tool for improving students’ performance in mockexams and, ultimately, in final exams. However, instructors should be mindful of the potential negativeeffects of feedback and strive to provide it in a constructive and supportive manner. In conclusion,feedback on students’ performance in mock exams can be a blessing or a curse, depending on how it isdelivered and received.